CITRATE IN MINERALIZED TISSUES. VI. THE EFFECTS OF DIETARY REHABILITATION WITH CALCIUM OR WITH VITAMIN D, OR WITH CALCIUM AND VITAMIN D, IN RATS PREVIOUSLY MAINTAINED ON A DIET DEFICIENT IN BOTH CALCIUM AND VITAMIN D. - Hartles, R; Leaver, A; Triffitt, J (1963)
Fifty weanling hooded rats were maintained for 8 weeks on a diet low in calcium and vitamin D. Similar groups were then transferred to diets adequate in calcium, or adequate in vitamin D, or sufficient in both respects. They were continued on these diets and representatives were killed at intervals during the 35 day period. The concentrations of calcium, phosphorus, and citrate in blood and bone were determined. When the deficient animals were rehabilitated with vitamin D alone, the concentration of citrate in bone was increased before that in the serum. Rehabilitation with calcium alone caused an increase in the concentration of serum citrate before any increase was observed in the bone. When the animals were transferred to a diet containing adequate supplies of calcium and vitamin D, the effects of both factors were distinguished since they occurred at different times. The implications of these results in relation to the possible function of citrate in bone are discussed. © 1963.